2016
DOI: 10.1093/jac/dkw056
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole dosing and therapeutic drug monitoring in children: experience from a paediatric tertiary care centre

Abstract: There is significant intra- and inter-individual variability in voriconazole concentrations in children, particularly in children <6 years of age. This warrants repeated TDM throughout treatment. Standardized guidelines for TDM and dose adjustment are required in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 34 publications
12
41
1
Order By: Relevance
“…Similar to the findings of many previous studies (14,15), 50% of children could not reach the target range at the initial trough concentration. The initial trough concentrations ranged from 0.02 to 9.35 mg/liter with high inter-and intraindividual variability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the findings of many previous studies (14,15), 50% of children could not reach the target range at the initial trough concentration. The initial trough concentrations ranged from 0.02 to 9.35 mg/liter with high inter-and intraindividual variability.…”
Section: Discussionsupporting
confidence: 90%
“…2. The study of Boast et al (15) showed that patients Ͻ6, 6 to 12, and Ͼ12 years of age required median intravenous doses of 8.8, 7.5, and 4.0 mg/kg twice daily, respectively, and these results were significant. These results were consistent with those obtained in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Our patient's final therapeutic dose (54 mg/kg/ day) was large compared to those reported in other published studies among pediatric patients. 1,[11][12][13] Use of every-8-hour dosing with the oral formulation was deemed necessary after multiple dosage adjustment using every 12 hours failed to overcome rapid hepatic clearance known to occur in infants.…”
Section: Discussionmentioning
confidence: 99%
“…Higher doses are used clinically in select patients, generally under the guidance of TDM. Institutional processes that result in delays in obtaining results may significantly impact TDM utilization, dosing practices, and patient outcomes [83, 118,207]. Recent dosing IV and oral experience for IFI in this age group include loading and maintenance doses up to 7-9 mg/kg [132,204,208].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…There is no FDA-approved dosing regimen for children <12 years of age, with the voriconazole label simply stating that safety and efficacy have not been established in this population [36]. A number of retrospective studies have additionally suggested that IV maintenance doses exceeding 8 mg/kg are necessary for children <6 years of age [11,104,207,209]. For serious Candida spp.…”
Section: Pediatric Dosingmentioning
confidence: 99%